Real estate market in studentified neighborhoods - Mira G. Baron; Ella R. Diamant (European Regional Science Association (ERSA), 2016)
This work explores the impact of 'Studentification' of a neighborhood on the profitability of investment in the housing market. The study breaks down the impact of students on the housing market into two areas: apartments for sale and apartments for rent. The Israeli housing market provides the data for the empirical analysis. The market is different from other markets by the fact that the Israeli real estate investments market is at most 29% of the housing market, since 71% are owner occupied apartments. In order to address profitability, different scenarios have been explored. The classical urban economics model (Alonso, 1964, Mills, 1967 and Muth, 1969) claims that purchasing or renting an apartment close to CBD (Central Business District) will save on commuting costs and on travel time. Resulting in a high price of housing close to the CBD, and a decrease in price further away. Students renting an apartment adjacent to an academic institution (a Studentified neighborhood) will be willing to pay a higher rent and landlords will be willing to pay more for a house. A contrary argument is that students are poorer than the average population. Their willingness to pay for rent is lower, and the landlords will decrease their willingness to pay for houses for investment. An alternative argument is that landlords have an aversion to rent to students due to the claims that they are noisy, generate litter, involved in vandalism and have a negative effect on the neighborhood. In contrast the students want to rent in a Studentified neighborhood. The alternative scenarios are examined empirically in a case study of rents and housing prices in Haifa, Israel, a metropolitan area in the north of Israel. There are two academic institutions with 30 thousand undergraduate students in the city. The neighborhoods adjacent to one of the academic institutions are defined as Studentified. The students of the other institution are not concentrated around it since there is no supply of housing units. We define the neighborhoods in the rest of the city as Non-Studentified. We analyze the price of apartments sold in the period 2005- 2011 and the price of rental units in the period 2011-2012. The empirical results show that Studentification affects positively the rental prices and negatively the price of assets. These results are consistent with landlords' aversion to locations adjacent to academic institutions. The results of the econometric analysis were used to calculate the Sharpe Ratio to examine profitability in Studentified vs. Non-Studentified neighborhoods. In Studentified neighborhoods the return on a house is higher than the rest of the city (the rent is higher and the price of an asset is lower). However, in these neighborhoods the standard deviation is higher (measuring the risk). Thus the Sharpe Ratio, which measures the excess return per unit of risk, is similar in all the neighborhoods of the city. These results which characterize Haifa do not necessarily reflect other cities. It will require repetition of these tests to see what characterizes Studentified neighborhoods elsewhere.
Keywords: R31; G11; 330; Housing Market; Hedonic Prices; Studentification; Sharpe Ratio